Intermuscular coherence during arm movement changes significantly with shoulder abduction and age, but not with limb dominance - Erwin, Andrew; Bartsch-Jimenez, Angelo; Azadjou, Hesam; Niyo, Grace; Valero-Cuevas, Francisco J. (Frontiers in Physiology, 2026)
IntroductionIntermuscular coherence (IMC) has the potential to become a clinical biomarker to quantify disruptions of shared neural drive to muscles in individuals with upper and lower extremity motor impairments. Here we test whether shoulder abduction, limb dominance and age affect IMC in unimpaired individuals to serve as a baseline for studies with clinical populations.MethodsTwenty-five unimpaired participants performed an established single-arm reaching task: rotating an ergometer in the horizontal plane while surface electromyography signals were recorded from the biceps, triceps and deltoids arm muscles. We compared IMC within the alpha, beta, and gamma frequency bands across three experimental factors: shoulder posture (neutral vs. abducted), arm (dominant vs. non-dominant), and age (younger {18–42 years. N = 12, 6 female} vs. older {51–74 years. N = 13, 7 female} adults).ResultsWe found that there was a significant effect on IMC due to shoulder posture in the alpha-band (F=22.4, p=0.0007), beta-band (F=44.6, p=5×10−5), and gamma-band (F=57.9, p=4×10−6). In addition, IMC was lower in the older group and significantly so in the alpha-band (F=6.6, p=0.03), but not in the beta- (F=4.5,p=0.07) and gamma-bands (F=0.52, p=0.42). Although the non-dominant arm tended to have higher IMC, no significant differences due to limb dominance were found.DiscussionWe provide what, to our knowledge, is the first overall comparison of patterns of IMC in unimpaired individuals across arms and the adult lifespan to help future studies quantify and interpret disruptions in neuromuscular control. Beyond confirming the expected increase in IMC with shoulder abduction, we critically demonstrate that age significantly affects IMC in the alpha-band associated with propriospinal sensorimotor processes. We speculate this may be a result of spinal reorganization of spinal motor nuclei due to α-motoneurone death with healthy aging. Given the supporting evidence in this study that limb dominance does not significantly affect IMC, common drive to muscles (as quantified by IMC) is likely driven by subcortical processes that predate the neural lateralization of human upper extremity function.